2017
DOI: 10.18805/ijare.a-4804
|View full text |Cite
|
Sign up to set email alerts
|

Effect dates of sowing and cutting time on seed yield and quality of alfalfa (Medicago sativa L.) CV. RL-88

Abstract: An experiment was carried to find out the effect of sowing dates and cutting time on seed yield and quality of alfalfa cv. RL-88. The results of the experiment revealed that, the significantly higher seed yield per plant (1.491 g), seed yield per plot (161.07 g) and seed yield (355.00 kg ha -1 ) was noticed in 15 th August sowing and the cutting carried out at 60 days after sowing. Whereas, the seed quality parameters of the resultant seeds viz., highest seed germination (95.00 %), seedling length (13.90 cm), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 2 publications
1
2
0
Order By: Relevance
“…Similar findings of yield reduction due to delay in last cut were reported by several other workers (Sinha and Rai, 1995;Singh and Kang, 2004;Puri et al, 2007). The present data is in conformity with the findings of Kumar and Patel (2017), Surinder et al (2019) and Singh et al (2019.…”
Section: Effect Of Cutting Regimes On Seed Yield and Qualitysupporting
confidence: 94%
“…Similar findings of yield reduction due to delay in last cut were reported by several other workers (Sinha and Rai, 1995;Singh and Kang, 2004;Puri et al, 2007). The present data is in conformity with the findings of Kumar and Patel (2017), Surinder et al (2019) and Singh et al (2019.…”
Section: Effect Of Cutting Regimes On Seed Yield and Qualitysupporting
confidence: 94%
“…These results are similar with the findings of Chaudhary et al (2020). Kumar et al (2017) concluded that the effect of sowing dates on plant growth parameters in alfa-alfa indicates a quantitatively more significant difference. Height of plant (69.46 cm), fresh weight of fodder (609.43 kg/ha) and dry weight of fodder (128.26 kg/ha) were significantly greater in the crop sown on 1 st July, but these qualities were decreased (8%, 4.2% and 8.6%, respectively) in 15 th August date sowing.…”
Section: Impact Of Agronomic Management Practices On Quality and Prod...supporting
confidence: 91%
“…In addition, we found that MtPAL2 was down regulated as the seed geminated, while the other PAL genes were up regulated. This phenomenon suggests that MtPAL genes play different roles in Medicago seed germination (Moawed, 2016;Kumar et al, 2017). The qRT-PCR results for MtPAL genes showed similar expression patterns as microarray data analysis indicated that microarray data are still useful for gene quantity.…”
Section: Expression Patterns Of Mtpal Genes In Different Tissuesmentioning
confidence: 79%